2020
DOI: 10.1039/d0sc00968g
|View full text |Cite
|
Sign up to set email alerts
|

N2Phos – an easily made, highly effective ligand designed for ppm level Pd-catalyzed Suzuki–Miyaura cross couplings in water

Abstract: A new, biaryl phosphine-containing ligand, N2Phos, forms a 1 : 1 complex with Pd resulting in an active catalyst at the ppm level for Suzuki–Miyaura couplings in water, enabled by an aqueous micellar medium. Notably, aryl chlorides are shown to be amenable substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In most cases (except for reactions that readily take place "on water"), the background reaction takes place to varying extents, but rarely with the same levels of conversion and ultimately, yields. Many of the synthetic bene-ts associated with using nanomicelles in water remain to be discovered, as only a few have been disclosed of late, including the "reservoir effect", 59 lipophilic ligand design, 38,120,121 and the "nano-to-nano" effect. 44 Clearly, when water is intimately involved, reactions can be governed by different "rules".…”
Section: Table 15mentioning
confidence: 99%
“…In most cases (except for reactions that readily take place "on water"), the background reaction takes place to varying extents, but rarely with the same levels of conversion and ultimately, yields. Many of the synthetic bene-ts associated with using nanomicelles in water remain to be discovered, as only a few have been disclosed of late, including the "reservoir effect", 59 lipophilic ligand design, 38,120,121 and the "nano-to-nano" effect. 44 Clearly, when water is intimately involved, reactions can be governed by different "rules".…”
Section: Table 15mentioning
confidence: 99%
“…One feature associated with this chemistry in water is the likelihood that the levels of residual palladium [5a–b,9] in each product will be below the imposed FDA limit of 10 mg/dose/day [15] . Using product 20 as a representative example, isolated without special processing, ICP‐MS analysis (Scheme 3a; Figure S2 for other representative compounds) indicated that only 2 ppm Pd was present.…”
Section: Figurementioning
confidence: 99%
“…[1b,4a] Moreover, and invariably, such methodologies take place in waste-generating organic solvents and oftentimes rely on an investment of energy in the form of elevated temperatures over time to achieve reasonable conversions. Thus, in the spirit of creating options for medicinal chemistry and beyond, [5] and with attention to the impact that such chemistry will have on the environment, [6] we now describe a new, indeed unique and reproducible [12] technology. This advancement enables late stage cyanations that addresses all of these major concerns, including its: (1) application to highly functionalized substrates;…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At andem, 1-pot process involving an initial ppm Pdcatalyzed [26] Suzuki-Miyaura cross-coupling could be performed given the same aqueous micellar conditions characteristic of both reactions (Figure 7). Thus,c yclopropanecontaining biaryl 25 could be accessed via 24 in an overall isolated yield of 86 %.…”
Section: Forschungsartikelmentioning
confidence: 99%